A hybrid framework for forecasting power generation of multiple renewable energy sources. (February 2023) - Zheng, Jianqin; Du, Jian; Wang, Bohong; Klemeš, Jiří Jaromír; Liao, Qi; Liang, Yongtu
Abstract: The accurate power generation forecast of multiple renewable energy sources is significant for the power scheduling of renewable energy systems. However, previous studies focused more on the prediction of a single energy source, ignoring the relationship among different energy sources, and failing to predict accurate power generation for all energy sources simultaneously. This paper proposes a hybrid framework for the power generation forecast of multiple renewable energy sources to overcome deficiencies. A Convolutional Neural Network (CNN) is developed to extract the local correlations among multiple energy sources, the Attention-based Long Short-Term Memory (A-LSTM) network is developed to capture the nonlinear time-series characteristics of weather conditions and individual energy, and the Auto-Regression model is applied to extract the linear time-series characteristics of each energy source. The accuracy and practicality of the proposed method are verified by taking a renewable energy system as an example. The results show that the hybrid framework is more accurate than other advanced models, such as artificial neural networks and decision trees. Mean absolute errors of the proposed method are reduced by 13.4%, 22.9%, and 27.1% for solar PV, solar thermal, and wind power compared with A-LSTM. The sensitivity analysis has been conducted to test the effectiveness of each component of the proposed hybrid framework to prove the significance of energy correlation patterns with higher accuracy and stability compared with the other two patterns. Graphical abstract: Image 1 Highlights: Propose a hybrid framework for power forecast of multiple renewable energy sources. Improve forecast accuracy by considering energy correlation patterns. Sensitivity analysis is conducted to discuss each information pattern. Method verified by a real renewable energy system case.